An overview of the synthetic routes to the best selling drugs containing 6-membered heterocycles - Baumann, Marcus; Baxendale, Ian R. (Beilstein Journal of Organic Chemistry, 2013)
This review which is the second in this series summarises the most common synthetic routes as applied to the preparation of many modern pharmaceutical compounds categorised as containing a six-membered heterocyclic ring. The reported examples are based on the top retailing drug molecules combining synthetic information from both scientific journals and the wider patent literature. It is hoped that this compilation, in combination with the previously published review on five-membered rings, will form a comprehensive foundation and reference source for individuals interested in medicinal, synthetic and preparative chemistry.
Keywords: heterocycles; medicinal chemistry; pharmaceuticals; six-membered rings; synthesis